Murraya koenigii (L.) Spreng and Tinospora cordifolia (Willd.) : Potential antimicrobials against Treponema denticola - an Invitro analysis - Shivakumar, Vanishree; Tegginamani , Anand S.; Annapurny Venkiteswaran; , Nurhayati Mohamad Zain; Mohd Sarmin, Nurul ’Izzah; Hassan , Eddy Hasrul (Journal of University Medical & Dental College, 2025)
BACKGROUND & OBJECTIVE: Endodontic infections are polymicrobial in nature and commonly involve anaerobic bacteria such as Treponema denticola, a spirochete also associated with periodontal disease. Increasing interest in herbal alternatives has led to the investigation of traditional medicinal plants for dental infections. However, the antibacterial activity of Murraya koenigii (L.) Spreng and Tinospora cordifolia (Willd.) against T. denticola has not been previously reported. This study aimed to evaluate the antibacterial efficacy, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) of ethanolic leaf extracts of M. koenigii and T. cordifolia against T. denticola. METHODOLOGY: An in vitro experimental study was conducted using the Kirby–Bauer disc diffusion method to assess the zone of inhibition (ZOI) of M. koenigii (Group 1) and T. cordifolia (Group 2) extracts against T. denticola. Triple antibiotic paste (Group 3) served as the positive control, while sterile water was used as the negative control. MIC and MBC values were determined using the serial dilution method. RESULTS: Group 1 exhibited a greater ZOI (18.09 ± 1.99 mm) compared to Group 2; however, both were significantly lower than the positive control (p < 0.001). MIC results indicated bacteriostatic activity for M. koenigii, whereas T. cordifolia demonstrated bactericidal effects. CONCLUSION: Both Murraya koenigii (L.) Spreng and Tinospora cordifolia (Willd.) showed promising antibacterial activity against T. denticola, suggesting their potential use as intracanal medicaments for reducing root canal pathogens.